Remote Global Alignment Error for Cycle Time Improvement of Pad Inductor Layer - Maidin, S.; Devadas, S.; Wara, T. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Lithography is the key process which transfers the pattern from mask to wafer and pad inductor layer is the last layer in photo masking. The cycle time for pad inductor layer increase in Silterra Malaysia by 32% of Global Alignment error per month. This induce success rate goes down as low as 50% for pad inductor layer. Long engineering time is taken during troubleshooting of the lot for expose and developing step by manually due to tool time constrain. Most of the lots undergo rework processes which results the cost per wafer to increase. The aim of this research is to reduce the cycle time for pad inductor layers by introducing the “Remote Global Alignment Error” (RGAE) method with alternative flow. This would avoid the pad inductor layers to be sent for rework if it encountered any global alignment error. The experimental result shows RGAE method able to reduce cycle time for pad inductor layer by 97%. This is due to when global alignment error occurs the lot will automatically track in RGAE method by selecting the rejected wafers for expose and developing process. This has eventually saved more time for split wafers which usually send for rework.